2018
DOI: 10.3389/fmicb.2018.01752
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Bacteria in Earth's Lower Stratosphere Resemble Taxa Detected in the Troposphere: Results From a New NASA Aircraft Bioaerosol Collector (ABC)

Abstract: Airborne microorganisms in the upper troposphere and lower stratosphere remain elusive due to a lack of reliable sample collection systems. To address this problem, we designed, installed, and flight-validated a novel Aircraft Bioaerosol Collector (ABC) for NASA's C-20A that can make collections for microbiological research investigations up to altitudes of 13.7 km. Herein we report results from the first set of science flights—four consecutive missions flown over the United States (US) from 30 October to 2 No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 98 publications
3
70
1
Order By: Relevance
“…The driving bacterial classes identified here were repeatedly found in other bioaerosol studies; Bacilli and Cyanobacteria were repeatedly identified with dust storms and long-range troposopheric transport, while Alpha-, Beta-and Gammaproteobacteria as well as Actinobacteria often characterised non-dust below the PBL air (Jeon et al, 2011;Maki et al, 2017;Smith et al, 2010Smith et al, , 2011Smith et al, , 2012Smith et al, , 2018. Some species of Bacilli are frequently detected in connection with dust events, and hence long-distance transport, and are seen as characteristic of Saharan and Chad desert sand events (Favet et al, 2013;Smith et al, 2010Smith et al, , 2012.…”
Section: What Drives the Differences?supporting
confidence: 75%
“…The driving bacterial classes identified here were repeatedly found in other bioaerosol studies; Bacilli and Cyanobacteria were repeatedly identified with dust storms and long-range troposopheric transport, while Alpha-, Beta-and Gammaproteobacteria as well as Actinobacteria often characterised non-dust below the PBL air (Jeon et al, 2011;Maki et al, 2017;Smith et al, 2010Smith et al, , 2011Smith et al, , 2012Smith et al, , 2018. Some species of Bacilli are frequently detected in connection with dust events, and hence long-distance transport, and are seen as characteristic of Saharan and Chad desert sand events (Favet et al, 2013;Smith et al, 2010Smith et al, , 2012.…”
Section: What Drives the Differences?supporting
confidence: 75%
“…Our results showed that, despite the similitudes in the bacterial diversity between our atmospheric samples and the previously reported ones, there are a number of important and stark differences. For example, we did not find any sequence related to Afipia sp., one of the main constituents of the troposphere community (>40% of total community) reported by DeLeon-Rodriguez et al (2013), as well as some of the most abundant families recently described by Smith et al (2018) in the lower stratosphere (such as Staphylococcaceae, Moraxellaceae, Lachnospiraceae and Ruminococcaceae), although we found a similar number of OTUS. Furthermore, one of the main components found in our samples related to Saharan intrusion, Microvirga sp., has not been reported previously in the consulted literature.…”
Section: Diversity Of Bacteria Sequences Were Affiliated With 27 Bacsupporting
confidence: 71%
“…Studies focusing on free tropospheric air microbial communities often present data from single campaigns or few flights (Schmale and Ross 2015;Techy et al 2010;Jimenez-Sanchez et al 2018;Smith et al 2018;Maki et al 2017;Xia et al 2013;Zweifel et al 2012) and have shown that microbes present in the free troposphere might originate from long-range travel (Maki et al 2017;Smith and David 2012;Smith et al 2011Smith et al , 2012Brown and Hovmøller 2002;Burrows et al 2009a, b). Air masses above and below PBL differ significantly in microbial composition.…”
Section: Introductionmentioning
confidence: 99%
“…Air masses above and below PBL differ significantly in microbial composition. Free tropospheric habitats tend to have more Firmicutes (Smith et al 2018;, Proteobacteria, Burkholderiales (DeLeon-Rodriguez et al 2013) and extremophile yeasts, Saccharomycetes and Microbotryomycetes (Els et al 2019). While the existence of either a stable (DeLeon-Rodriguez et al 2013) or a highly variable (Zweifel et al 2012) extremophile free tropospheric PBA community is disputed, generally few studies addressing the question were mainly performed over marine and oceanic regions (DeLeon-Rodriguez et al 2013).…”
Section: Introductionmentioning
confidence: 99%